Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15446/rev.colomb.quim.v46n1.62830
|View full text |Cite
|
Sign up to set email alerts
|

Dolabellane diterpenes from the Caribbean soft corals Eunicea laciniata and Eunicea asperula and determination of their anti HSV-1 activity

Abstract: Los dolabellanos son diterpenos con importante actividad antiviral, la mayor parte de los estudios se han realizado con compuestos aislados de algas pardas del género Dictyota. Los corales blandos son también una importante fuente de dolabellanos, pero el potencial antiviral de éstos ha sido muy poco estudiado. Como parte de nuestra búsqueda de compuestos bioactivos a partir de fuentes marinas, se llevó a cabo el estudio químico de los dolabellanos presentes en los octocorales Eunicea laciniata y Eunicea asper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The presence of a hydroxy group (-OH) on C-13 in compound 158-160 affects the compound’s anti-HSV-2 strength ( González et al, 2010 ). Dolabellane diterpenes, (1R, 3R, 4R, 7R, 8R, 11S)-di-3,4:7,8-epoxy-13-keto-dolabell-12(18)-ene (123) from Eunicea laciniata and (1R, 3E, 4R, 7R, 8R, 11S)-di-7,8-epoxy-13-keto-dolabell-3,12(18)-diene (124) from Eunicea sperula has anti-HSV-1 activity with inhibition values of 42.6% and 73.7% ( Amaya-Garcia et al, 2017 ). Nigella damascene seeds contain dolabellane diterpenes, damasterpenes I-III (129-131) , and damasterpenes V-VIII (125-128) .…”
Section: Herpes Virusmentioning
confidence: 99%
“…The presence of a hydroxy group (-OH) on C-13 in compound 158-160 affects the compound’s anti-HSV-2 strength ( González et al, 2010 ). Dolabellane diterpenes, (1R, 3R, 4R, 7R, 8R, 11S)-di-3,4:7,8-epoxy-13-keto-dolabell-12(18)-ene (123) from Eunicea laciniata and (1R, 3E, 4R, 7R, 8R, 11S)-di-7,8-epoxy-13-keto-dolabell-3,12(18)-diene (124) from Eunicea sperula has anti-HSV-1 activity with inhibition values of 42.6% and 73.7% ( Amaya-Garcia et al, 2017 ). Nigella damascene seeds contain dolabellane diterpenes, damasterpenes I-III (129-131) , and damasterpenes V-VIII (125-128) .…”
Section: Herpes Virusmentioning
confidence: 99%
“…3.1 | Effect on cell viability of the 32 marine diterpenes A library of 32 diterpenes (Figure S1) was built, among them 12 have briarane nucleus, 17 have cembranoid nucleus (six semisynthetic (23-28) and eleven without synthetic modifications), and three have dolabellane nucleus. These compounds were isolated from Eunicea, Plexaura, Pseudoplexaura, and Erythropodium octocorals, and their chemical structures were fully stablished in previous works (Amaya García et al, 2017;Castellanos et al, 2018;Look et al, 1984;Molina et al, 2020;Rice et al, 1970;Tello et al, 2009Tello et al, , 2012Tello et al, , 2013. The MTT assay was used to determine cell viability against three human cancer cell lines (A549-human lung cancer, MCF7-human breast adenocarcinoma, and PC3-human prostate cancer).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies indicate that dolabellanetriol’s mechanism of action is consistent with a non-nucleoside reverse transcriptase inhibitor (NNRTI). , Another source of diterpenes with different structural arrangements, including other dolabellanes, is soft corals. , Yet, the potential of soft corals as a source of antiviral dolabellanes has not been deeply explored, as there are only a few studies in this field. Previous work from our research group revealed that dolabellanes isolated from Eunicea laciniata , collected at the Colombian Caribbean Sea, inhibited HSV-1 replication, whereas semisynthetic derivatives obtained from dolabellatrienone ( 1 ) exhibited increased anti-HIV activity. , A noteworthy difference between dolabellanes obtained from Eunicea soft corals and Dictyota brown algae is the opposite absolute configuration in the fused bicyclic ring system. These findings suggest that soft corals can also contribute to the discovery of more antiviral dolabellanes, and it is hypothesized that, regardless of the configuration of the bicyclic core, oxygen-containing functional groups are the main factor that influence the antiviral activity of dolabellane diterpenes.…”
mentioning
confidence: 78%